2022
DOI: 10.52633/jms.v4i2.193
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Customer Trust and Positivity of Perceived Customer Service Skill on the Confidence of Online Shopping

Abstract: With the economy's continuous development, consumers become more mature and rational, so many keen enterprises gradually shifted their focus from the initial product development to "customer service skill" and thus obtained a good market return. Especially for the online shopping activities carried out in the virtual (digital) way, due to the particularity of its channel, it is more important to study the experience of its customers in online consumption. In addition, shopping websites and businesses selling g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This conforms with the findings of previous empirical studies which revealed similar findings showing that online buying intentions can be significantly predicted by WebQual factors such as ease of use (Cho and Sagynov, 2015;Hermawan, 2022) and visual appeal (Gazal & Rababbah, 2019). Similarly, and consistent with previous empirical findings (e.g., Chang et al, 2014;Jeon et al, 2016;Zia et al, 2022), our research shows the significance of WebQual dimensions in predicting customer perceived trust. Moreover, results suggest a significant positive effect of perceived trust on behavioral intentions.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 92%
“…This conforms with the findings of previous empirical studies which revealed similar findings showing that online buying intentions can be significantly predicted by WebQual factors such as ease of use (Cho and Sagynov, 2015;Hermawan, 2022) and visual appeal (Gazal & Rababbah, 2019). Similarly, and consistent with previous empirical findings (e.g., Chang et al, 2014;Jeon et al, 2016;Zia et al, 2022), our research shows the significance of WebQual dimensions in predicting customer perceived trust. Moreover, results suggest a significant positive effect of perceived trust on behavioral intentions.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 92%
“…El presente estudio ha identificado aspectos fundamentales sobre la atención al cliente en Marketplace de Facebook en la ciudad de Cuenca, que contrastan y a la vez se alinean con las tendencias señaladas en el estado del arte de la atención al cliente en marketplaces digitales. En este contexto, los hallazgos revelan que una proporción significativa de emprendedores en Cuenca ofrece respuestas dentro de las primeras 24 horas tras la consulta, lo cual se correlaciona con el énfasis en la telepresencia y la confianza discutido por Zia et al (2022). La rápida respuesta no solo refleja la capacidad técnica y la preparación tecnológica de los emprendedores, sino también una disposición para fomentar una experiencia de usuario satisfactoria y confiable, elementos que son determinantes en la percepción de un servicio de calidad en el entorno digital.…”
Section: Discussionunclassified
“…El servicio al cliente en marketplaces digitales y la experiencia del consumidor online ha sido objeto de numerosos estudios recientes, reflejando la evolución y las dinámicas actuales de estos entornos. En esta línea, Zia et al (2022), resaltan la importancia de la telepresencia, el placer y la confianza en el proceso de compra online. Este estudio demuestra cómo los elementos intangibles como la percepción del servicio y la interacción digital impactan significativamente en la experiencia y satisfacción del cliente en entornos virtuales.…”
Section: Estado Del Arteunclassified
“…Although trust has been reported to be one of the main factors affecting the transactions on online platforms (Guo et al , 2017), most of the studies in the literature examined trust from the standpoint of buyers, not sellers (i.e. Gefen et al , 2003; Koh et al , 2012; Mou et al , 2020; Pavlou and Gefen, 2004; Kumar et al , 2018; Sfenrianto et al , 2018; Qalati et al , 2021; Zia et al , 2022). As for those investigating the subject from the standpoint of sellers, Cui et al (2019) reported that trust in online selling platforms, along with benefits, explains the two-thirds of the sellers’ intention to sell on these platforms.…”
Section: Literature Reviewmentioning
confidence: 99%